Flexural Behaviour and Numerical Simulation on High Strength Nano Silica Concrete - Jaishankar, P; Mahalakshmi, S; Saravana Raja Mohan, K (International Journal of Engineering and Technology, 2018)
Effects on Flexural behavior attribute of nano SiO2 is a most widely used material in cement and concrete to boost the completion because of its pozzolonic reactivity moreover the pore stuffing effect. The results were obtained for mechanical strength, by assorted the reduced contents of 5%, 10%, 15% and 20% NS by volume fraction of cement. For further study, Finite Element Software ANSYS 10.0 is used for modeling and analysis by nonlinear steady flexural strength of the beam by two points loading.Â  The micro structure XRD, XRF diagnosing the migrate properties of high strength concrete, such as permeability and ion transports. Nano silica into concrete mix has shown result of increasing mechanical strength, and flexural behaviour of high strength nano silica concrete. The numerical modeling and experimental inspection circulate that the optimal reduced content of cement with ns is around 15 % of greatest strength increased.Â